Effect of the foliar application of biological preparations in apple (malus domestica borkh.) orchards on the formation of the fruits quality indices - Вінцковська, Ю. Ю. (Scientific Progress & Innovations, 2016)
The author presents the results of studying (2013–2015) the effects of the biological preparations «Atonik Plus» and «Vapor Gard» foliar application in apple orchards on the formation of fruits quality indicators (the content of dry soluble substances, organic titrate acids and sugars). The object of the research was the summer variety Yamba. The usage of «Atonik Plus» before the second wave of the ovary abscission and harvesting the crop increased the content of dry soluble substances and sugars, and reduced the accumulation of titrated organic acids in fruits. This application improved their taste. The best variant of the antitranspirant «Vapor Gard» was spraying at the first wave of the ovary abscission and before harvesting, namely: the sugar content in fruits increased as it is compared to the control.